MUSTAHIQ ZAKAT FITRAH DAN RELEVANSINYA DENGAN KEWAJIBAN MENUNAIKANNYA BAGI SETIAP MUSLIM (Telaah Pendapat Imam Malik W. 178 H) - Mushthafa, Mushthafa (IAIN Batusangkar, 2019)
It is different from the opinion of other religious scholars who state that mustahiq of zakat fitrah is the same as mustahiq of zakat mall as it is Allah's command in QS. Al-Taubah verse 60. Imam of the Maliki School and some Malikiyah scholars argued that mustahiq of zakât fitrah is a indigent and poor group, this is based on instructions of Rasulullah SAW. The existence of ikhtilâf in providing group boundaries for this mustahiq of zakât fitrah will be very interesting to be investigated further, especially if it is associated with the obligation to carry out the order zakât fitrah for every Muslim and wisdom contained in the order zakat fitrah.